2017
DOI: 10.1155/2017/5210708
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations of the Square Lid Driven Cavity Flow of Bingham Fluids Using Nonconforming Finite Elements Coupled with a Direct Solver

Abstract: In this paper, numerical simulations are performed in a single and double lid driven square cavity to study the flow of a Bingham viscoplastic fluid. The governing equations are discretized with the help of finite element method in space and the nonconforming Stokes elementQ~1/Q0is utilized which gives 2nd-order accuracy for velocity and 1st-order accuracy for pressure. The discretized systems of nonlinear equations are treated by using the Newton method and the inner linear subproablems are solved by the dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Starting with the pioneering works by Mosolov and Miasnikov [6] and Duvaut and Lions [7], a large number of mathematicians have worked on the theoretical analysis of Bingham fluids and other similar viscoplastic media (see [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and the references therein).…”
Section: Remarkmentioning
confidence: 99%
“…Starting with the pioneering works by Mosolov and Miasnikov [6] and Duvaut and Lions [7], a large number of mathematicians have worked on the theoretical analysis of Bingham fluids and other similar viscoplastic media (see [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and the references therein).…”
Section: Remarkmentioning
confidence: 99%
“…Such approaches with some comparisons are discussed in [13]. Some recent studies on Bingham fluids are reported in [14][15][16]. Over the last two decades or so, flow around obstacles has been emerged as a very important benchmark problem due to its extensive applications in engineering science [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The materials like toothpaste and tomato ketchup are yield stress oriented. The rheology of such is investigated by many researchers [18][19][20][21][22][23][24]. There are some recent discussion and hypothesis about the existence of yield stress.…”
Section: Outletmentioning
confidence: 99%